Research on situation assessment of active distribution networks considering cyberattacks - Li, Jun’e; Liang, Jiaqi; Liu, Quanying; Qi, Donglian; Zhang, Jianliang; Chen, Yangrong (Frontiers in Energy Research, 2022)
With the rapid development of integrated energy system, the large-scale and high-permeability access of distributed generations (DGs) is making the distribution networks develop into active distribution networks (ADNs). The increased complexity of ADNs also increases the vulnerabilities for cyberattacks. It is a new challenge how to evaluate the situation of an ADN so as to support the decision-making of grid control policies in the condition of cyberattacks probably occur. Hence, in this paper, we proposed a method of situation assessment for ADNs considering cyberattacks. This method is aggregated by two parts. 1) An index system is presented, which includes the indexes of DGs stability, the indexes of security risk considering cyberattacks along with the traditional safety indexes. 2) The entropy weight method is used to assign weights to each index, and taking the normal operation status of ADNs as the reference scenario, an operating situation assessment method for ADNs is proposed based on grey correlation analysis method. Finally, in order to verify the effectiveness of the proposed index system and assessment method, 12 attack scenarios are established from three categories: attacks on DGs, attacks on controllable loads and attacks on both DGs and loads, and the situation of the ADN, a case based on IEEE 33-node standard distribution system, is evaluated under each scenario.